The Relationship between Sleep Quality and Blood Pressure in Patients with Hypertension - Wahid Nur Alfi; Roni Yuliwar (Jurnal Berkala Epidemiologi, 2018)
Background: Hypertension is one of the non-communicable diseases (NCDs) that is commonly found in Indonesia and the majority of people suffering from hypertension are females with the percentage of 28,80% with late detection of hypertension leads to serious health problems such as organ failure. Lousy sleeping habit or lack of sleeping hours may increase the risk of hypertension, heart disease, and other cardiovascular diseases. Purpose: This study aimed to investigate the relationship between sleep quality with patients’ blood pressure in public health center (puskesmas) in Mojolangu region of Malang city. Methods: The study was analytic observational with cross-sectional study design. The population of this study was all hypertension patients registered in puskesmas Mojolangu. Respondents were selected based on the period of hypertension, so that were 30 respondents included through inclusion and exclusion criteria. The dependent variable was blood pressure, while the independent variable was sleep quality. Data were analyzed through the contingency coefficient. Results: Most of the patients with abnormal blood pressure were females with the percentage of 53,30%, aged 41-60 years old (43,30%) with lousy sleep quality (66,70%). There was a strong correlation between blood pressure in patients with hypertension and sleep quality by 0,65. Conclusion: Most of the respondents with lousy sleep quality will have high blood pressure. Therefore, assistance will be needed on hypertension patients.